Thermodynamics of dye removal from aqueous solution using adlai shell (Coix lacryma-jobi L.) adsorbents - Vargas, Janice P.; De Luna, Mark Daniel G. (Quezon City College of Engineering, University of the Philippines Diliman, 2015)
The thermodynamics of Reactive Yellow 145 (RY 145), Methylene Blue (MB), and Methyl Orange (MO) from aqueous solutions using adlai shell adsorbents were determined through batch adsorption studies. The adsorbents carbonized adlai (CA), acid- treated carbonized adlai (ACA) and base-treated carbonized adlai (BCA) shells were characterized using Scanning Electron Microscopy (SEM) and Fourier transform infrared (FTIR) analysis. The isotherm data were fitted well to the Langmuir isotherm (R2 =0.877 to 0.996) and validated by its RL values (0.242 to 0.985). The kinetics of the adsorption system is best described by pseudo-second order (R2 = 0.888 to 0.999). The high coefficient of determination (R2 = 0.8963 to 0.999) for the intraparticle diffusion and the linear plots indicate that some degree of boundary layer control the adsorption process and shows that intraparticle is not only the rate-determining step. The activation energy values (Ea≥ 66.70 kJ mol-1) derived from Arrhenius equation proves that the adsorption mechanisms chemisorption. The negative values of ∆G° indicates that the adsorption is thermodynamically feasible and is spontaneous process. The positive values of ∆H° and ∆S° indicate that the process was endothermic and suggests an increase in the randomness at the solid/solution interface during adsorption. The results revealed that the adlai shell has potential as an adsorbent for dye removal from aqueous solution.
Thesis (M.S. Environmental Engineering)--University of the Philippines Diliman
Keywords: Water -- Purification -- Adsorption; Sewage -- Purification -- Color removal; Adlai shells